(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article provides information about the field of cyber risk and accounting, and this article also provides several methods for studying the field of accounting and cyber risk. Of course, accounting and cyber security are fields related to the modern world. And the development of these professions significantly affects the economy. brings positive benefits.